Analysis of Mudharabah and Musyarakah Financing on the Growth of Islamic Bank Assets in Indonesia - Pamikatsih, Mutia; Astrina, Fenty; Kimsen, Kimsen; Raspati, Gunawan; Sudarmanto, Eko (West Science Social and Humanities Studies, 2026)
This study aims to analyze the influence of mudharabah and musyarakah financing on the growth of Islamic bank assets in Indonesia. The research employs a quantitative approach using primary data collected from 200 respondents through a structured questionnaire measured with a Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability testing, classical assumption testing, multiple linear regression, and hypothesis testing. The results indicate that mudharabah financing has a positive and significant effect on Islamic bank asset growth with a regression coefficient of 0.382 and a significance value of 0.000. Similarly, musyarakah financing shows a positive and significant influence with a regression coefficient of 0.417 and a significance value of 0.000. Simultaneously, both financing schemes significantly contribute to asset growth, as indicated by an F-value of 65.721 and an R Square of 0.401. These findings suggest that profit-sharing financing plays an important role in strengthening asset expansion and financial sustainability within Islamic banking institutions. The study provides practical implications for Islamic bank management to optimize partnership-based financing strategies and contributes to the literature on Islamic financial performance in Indonesia.